Highlights in the history of the American press : a book of readings - Ford, Edwin H. (Edwin Hopkins), 1891-1964.; Emery, Edwin (Minneapolis : University of Minnesota Press, 1954)
The articles collected in this volume present a vivid panorama of American journalistic history from its antecedents in the English ballad singers to the press giants of modern times. Since there is probably no single force that has played a greater role.
Part 1. The rise of an English press -- part 2. A colonial press in the English pattern -- part 3. The revolution and new republic : a nationalistic press -- part 4. Jacksonian democracy and a popular press -- part 5. Post civil war : a press in transition -- part 6. Mass circulation : the press giants.
Includes bibliographical references and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: American newspapers -- History; Press -- United States -- History; Journalism -- United States -- History; Journaux américains -- Histoire; Presse -- États-Unis -- Histoire; LANGUAGE ARTS & DISCIPLINES -- Journalism; LITERARY COLLECTIONS -- American -- General; American newspapers; Journalism; Press; United States; History